2016
DOI: 10.1186/s12955-016-0573-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Satisfaction with Life Scale (SWLS): secondary analysis of the Mexican Health and Aging Study

Abstract: BackgroundThe Satisfaction with Life Scale (SWLS) has been widely used and has proven to be a valid and reliable instrument for assessing satisfaction with life in diverse population groups, however, research on satisfaction with life and validation of different measuring instruments in Mexican adults is still lacking. The objective was to evaluate the psychometric properties of the Satisfaction with Life Scale (SWLS) in a representative sample of Mexican adults.MethodsThis is a methodological study to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
74
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 26 publications
14
74
0
3
Order By: Relevance
“…36,39 Moreover, it has satisfactory test-retest reliability and adequate internal consistency, which typically ranges from .74 to .87. 36,37,39,40 In the current study, Cronbach's α was good and stood at .84.…”
Section: Subjective Well-beingmentioning
confidence: 47%
See 1 more Smart Citation
“…36,39 Moreover, it has satisfactory test-retest reliability and adequate internal consistency, which typically ranges from .74 to .87. 36,37,39,40 In the current study, Cronbach's α was good and stood at .84.…”
Section: Subjective Well-beingmentioning
confidence: 47%
“…The SWLS has been shown to possess multimethod concurrent validity with other well‐being constructs, including an association with Facebook usage and a negative association with measures of psychopathology . Moreover, it has satisfactory test‐retest reliability and adequate internal consistency, which typically ranges from .74 to .87 . In the current study, Cronbach's α was good and stood at .84.…”
Section: Methodsmentioning
confidence: 58%
“…Although the internal consistency, reliability and validity of the SWLS were extensively supported (Diener et al 1985;Diener 1993, 2008;Vassar 2008), important issues were raised about the scale"s dimensionality. While some studies supported the initially intended one-factor structure (e.g., Lorenzo-Seva et al 2019;Ortuño-Sierra et al 2019;López-Ortega et al 2016), other ones suggested the presence of a temporal dimension, requiring the distinction between satisfaction with the present and past life (e.g., Bai et al 2011;Clench-Aas et al 2011). In addition, investigating the sensitivity of the SWLS along the latent trait continuum is of fundamental importance, considering that the scale is often used to evaluate change, impact, and progress on individual and societal levels.…”
Section: Findings From South Africa and Italymentioning
confidence: 99%
“…It promotes activity and better coping with difficult situations (López‐Ortega et al. ). In other words, satisfaction with life is a result of a balance between the current situation and personal norms (Loewe et al.…”
Section: Background Including the Literature Reviewmentioning
confidence: 99%
“…Satisfaction with life is an overall assessment of the life satisfaction of a given person with regard to personal standards. It promotes activity and better coping with difficult situations (L opez-Ortega et al 2016). In other words, satisfaction with life is a result of a balance between the current situation and personal norms (Loewe et al 2014).…”
Section: Background Including the Literature Reviewmentioning
confidence: 99%